2013
DOI: 10.2147/cia.s48325
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dementia in Al-Quseir city, Red Sea Governorate, Egypt

Abstract: Dementia is one of the most important public health problems as a result of the rapid increase in the number of elderly persons worldwide. Improvement of prevention strategies and caring for people with dementia should be undertaken. We performed a door-to-door study to screen all subjects aged 50 years and older (n=4,329 of 33,285 inhabitants) in Al-Quseir city. The screening was performed by 3 neuropsychiatrists, using a modified form of the Mini-Mental State Examination. Suspected cases were subjected to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…1419 The six eligible studies were conducted in four governorates in Egypt between 1993 and 2013 (Table 1; Figure 2). Two studies were conducted in the New Valley governorate,15,16 and two were conducted in the Red Sea governorate 17,18. However, it is not stated whether the studies included the same individuals.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1419 The six eligible studies were conducted in four governorates in Egypt between 1993 and 2013 (Table 1; Figure 2). Two studies were conducted in the New Valley governorate,15,16 and two were conducted in the Red Sea governorate 17,18. However, it is not stated whether the studies included the same individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were performed on subjects aging ≥50,1518 and the other two studies were conducted on people aging ≥60 14,19. Most studies did not report substance-induced dementia or dementia due to alcohol because of the sociocultural characteristics of the communities 14,1618. In addition, two studies reported dementia in communities with high prevalence of Parkinson’s disease,12,19 one study reported high prevalence of cerebral palsy in the community,17 and one study reported dementia due to chronic renal diseases or hepatic disease because of schistosomiasis 14.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations